Parameter optimization with particle swarm in a continuous cast mold - González Rondón, Yordy (2021)
To adjust the parameters that influence the appearance of defects in the steel in the continuous casting mold, a particle swarm optimization algorithm (PSO) was developed using process models. The study considered multiple objectives with multiple restrictions and the results were compared with those reported by a teaching-learning-based optimization algorithm (TLBO). We conclude that the PSO has a good capacity to determine the parameters of the mold, and with it, it is possible to achieve an optimal solution without requiring great computational efforts.